2003
DOI: 10.1890/01-0619
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Plant Disease on a Continental Scale: Role of Aerial Dispersal of Pathogens

Abstract: Successful transmission of plant diseases over long distances through the atmosphere depends on the reproductive rate of the pathogens, on the carrying capacity of the source locality, on atmospheric turbulence, stability, and wind speed, and on the survival of spores during exposure to inhospitable temperature and humidity and to UVB radiation from the sun. These interacting factors were incorporated into a model to estimate the rate and extent of seasonal incursions of disease from southern into northern are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
152
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(163 citation statements)
references
References 15 publications
9
152
1
1
Order By: Relevance
“…Strong filtering exists between the different phases; successful invasion is a rare event such that only a small fraction of alien species survive to pass through and establish themselves in a novel environment. Both host availability (as a suitable ecological niche) and environmental conditions (extremes of temperature, moisture, and UV radiation) in the new location place strong limitations on a pathogen's survival, its ability to reproduce and disperse, and subsequently spread [19,20]. These factors act as a strong selection filter leading to rapid adaptation to new environmental conditions and rapid evolution and exploitation of novel hosts [20].…”
Section: Novel Environments Novel Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong filtering exists between the different phases; successful invasion is a rare event such that only a small fraction of alien species survive to pass through and establish themselves in a novel environment. Both host availability (as a suitable ecological niche) and environmental conditions (extremes of temperature, moisture, and UV radiation) in the new location place strong limitations on a pathogen's survival, its ability to reproduce and disperse, and subsequently spread [19,20]. These factors act as a strong selection filter leading to rapid adaptation to new environmental conditions and rapid evolution and exploitation of novel hosts [20].…”
Section: Novel Environments Novel Hostsmentioning
confidence: 99%
“…Understanding novel forest pathogen introductions and the factors driving invasion success requires a deeper understanding of the invasion sequence that is conditioned by local or long-distance transport mechanisms from their native habitat to a novel environment, as well as environmental conditions and ecological factors determining an organism's survival and reproducibility, and any population and community effects affecting their dynamics across a range of spatial and temporal scales (see Figure 1). (extremes of temperature, moisture, and UV radiation) in the new location place strong limitations on a pathogen's survival, its ability to reproduce and disperse, and subsequently spread [19,20]. These factors act as a strong selection filter leading to rapid adaptation to new environmental conditions and rapid evolution and exploitation of novel hosts [20].…”
Section: Novel Environments Novel Hostsmentioning
confidence: 99%
“…Fungal spores causing severe agricultural diseases are dispersed in rare events over hundreds or even thousands of kilometers . Transport through the air is profoundly affected by turbulence over a wide range of spatial scales (Aylor 2003;Nathan et al 2005).…”
mentioning
confidence: 99%
“…A recent study addressing the above problems showed that dispersal of the wheat stripe or yellow rust fungus (Puccinia striiformis) fitted a power-law model well if enough sufficiently distant spore traps were used (Sackett and Mundt 2005). Moreover, although several physical processes underlie wind dispersal, theoretical arguments strongly propose that LDD of small objects can be modeled by a single function that will have inverse power-law behavior in the tails (Shaw 1995;Kot et al 1996;Stockmarr 2002;Aylor 2003;Shaw et al 2006). Uplift is the most important factor for heavier propagules but many factors are equally important for smaller objects such as spores (Nathan et al 2005).…”
mentioning
confidence: 99%
“…The models we had in mind are based on spatial point processes as in Section 4.4 and in Austerlitz et al (2004), Klein et al (2006a), Minogue (1989) and Tufto et al (1997). There also exist models including LDD which are based on Gaussian puff or differential equations (Aylor, 1987(Aylor, , 2003Ferrandino, 1993). In these models, which take the vertical dimension into account, the turbulence allows the particles to escape the canopy and to be transported over long distances.…”
mentioning
confidence: 99%